(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2022)
Experiment was conducted on mango at ICAR-Indian Institute of Soil and Water Conservation, Dehradun during 1995-2020. Mango cultivar ‘Mallika’ was the most vigorous and attained maximum plant height (6.80 m), canopy volume (220.25 m3) produced highest fruit yield (90.81 kg tree-1), litter production (5.35 tha-1), fine root production (847.21 g m-2 yr-1) and conserved 10.90 cm moisture in the soil profile upto 1.20 m depth. Whereas the lowest plant height (4.50 m), canopy volume (147.73 m3) in Amrapali cultivar, soil moisture conservation and lowest fruit yield (50.31 kg tree-1) in Ramkela were recorded in 25 years of orchard life and 20 Year of fruiting life of mango. The maximum fruit qualities like fruit weight (g), pulp content (%), totals soluble solids (0Brix), total sugar (%), reducing sugar (%), non-reducing sugar, β carotene (%) in Mallika cultivar whereas maximum acidity (%) and Vit.-C in Ramkela cultivar of mango were observed during 1995-2020 on degraded lands. The biomass productivity comprising stem, branches and roots was the highest in Mallika (82.37 Mg ha-1), carbon stock (40.02 Mg C ha-1) with carbon sequestration rate (1.60 Mg C ha-1yr-1) followed by Bombay green (1.50 Mg C ha-1yr-1) and Langra (1.48 Mg C ha-1yr-1). Net present value of mango cultivars ranged from 32,068 USD in Mallika to 20,514 USD in Bombay Green cultivars of mango. The benefit cost ratio ranged from 3.26 (Mallika) to 2.0 (Bombay Green), thereby presenting adequate choice to the cultivators / growers to select the appropriate cultivars for specialization. The Mallika cultivar of mango outperformed considering demand of pulp/juice industries and Ramkela cultivar well qualified for pickle industries under degraded lands.